(untitled) (Salam International Academic Journal, 2025)
Comparing Shar‘i Hijrah (legal migration according to Islamic law) and contemporary migration is a significant and valuable topic from the perspectives of religion, history, social justice, and human rights. This study is based on a descriptive-analytical research method, incorporating both the description of Islamic sources and historical realities, as well as an analytical examination of legal and social phenomena. In this research, the term Hijrah is defined according to Islamic jurisprudence as the act of a believing person relocating from one place to another in order to avoid oppression, trials (fitnah), and the prevention of practicing one’s faith freely. In contrast, migration or displacement in modern legal texts is understood as the process—either permanent or temporary—of individuals relocating due to economic, social, security-related, or natural factors. Additionally, terms such as asylum, forced migration, and persons under temporary protection are analyzed from the perspective of international law to better understand the modern dimensions of displacement. The aim of this research is to clarify the conceptual, value-based, and legal differences and similarities between Shar‘i Hijrah and contemporary migration. The study seeks to demonstrate that, although the two phenomena may appear similar on the surface, each represents a distinct reality in terms of purpose, conditions, legal implications, and human dignity. Furthermore, this research offers approaches for addressing the humanitarian and legal challenges faced by migrants, with the goal of fostering interaction between Islamic values and contemporary human rights frameworks.